Application of contextual teaching and learning (CTL) approach in the development of local environment-based curriculum - Zainul Arifin; Azkiya Jihadi A’la; Laela Lutfiana Rachmah; Alfarobi Ahmad Sulaiman (Universitas Islam Negeri Raden Intan Lampung, 2026)
Background: The integration of local environmental potential into early childhood education is important for creating meaningful and contextual learning experiences. However, many schools still face difficulties in connecting curriculum content with students’ real-life environments. Objective: This study aims to analyze the development of a local environment-based curriculum at Pembina Tana Tidung State Kindergarten through the Contextual Teaching and Learning (CTL) approach. Methods: This study employed a mixed-method approach through observation, interviews, document analysis, and questionnaires involving teachers and school stakeholders. Result: The findings show that CTL improved curriculum integration through contextual learning activities based on local environmental potential. Quantitative results revealed that 82% of teachers improved their competence in designing contextual lesson plans, while 78% of students demonstrated higher participation and learning motivation. Students also showed better critical thinking and simple problem-solving abilities during learning activities. Conclusion: The study concludes that CTL effectively supports sustainable local curriculum development by strengthening teacher competence and creating authentic learning environments in early childhood education.